Developing Strategies For Effective Knowledge Management (KM) In University Libraries In Nigeria - Edem, Nkoyo B.; Ani, O. E.; Ntui, Aniebiet (Journal of Knowledge Management Practice, 2011)
The paper examines Knowledge Management (KM) as a new concept for the development of university libraries in the emerging digital academic environments; and explores strategies for effective KM in Nigerian university libraries. A questionnaire survey was used as instrument for data collection with academic librarians as respondents. The findings of the study indicate that human resource development, provision of ICT infrastructure, and capacity building in ICT were the highest ranked strategies toward effective KM in Nigerian university libraries. The paper recommends that adoption of these strategies toward effective KM in university libraries would make Nigerian universities to be competitive in the global academic community.